Chronic neuromuscular electrical stimulation improves muscle mass and insulin sensitivity in a mouse model - Lotri-Koffi, Adiel (Sci Rep, 2019)
Muscle wasting reduces functional capacity and increases cardiometabolic risk in chronic disease. Neuromuscular electrical stimulation (NMES) of the lower limb has been shown to reverse muscle wasting in these patients but its effect on cardiometabolic health is unclear. We investigated a mouse model of in-vivo non-invasive chronic NMES on muscle mass, insulin sensitivity and arterial blood pressure (BP). Twenty-three C57BL6 mice underwent unilateral NMES or sham training over 2.5 weeks while anesthetized by isoflurane. Lower limb muscle mass and the stimulated limb to non-stimulated limb muscle mass ratio were compared between groups (NMES vs. sham). Insulin sensitivity was assessed 48 h after training using an intraperitoneal insulin tolerance test (ITT) and BP was assessed before and after training using the tail-cuff technique. After training, muscle mass increased in NMES vs. sham (416 ± 6 vs. 397 ± 6 mg, p = 0.04) along with the ratio of muscle mass (+3 ± 1% vs. −1 ± 1% p = 0.04). Moreover, insulin sensitivity improved in NMES vs. sham (average blood glucose during ITT: 139.6 ± 8.5 vs. 161.9 ± 9.0 mg/dl blood, p = 0.01). BP was decreased in both groups, although it is likely that the effect of NMES on BP was dampened by repetitive anesthesia. The metabolic benefit of NMES training could be of great utility in patients with chronic disease. Moreover, the clinical-like mouse model of NMES is an effective tool to investigate the systemic effects of local muscle strengthening.